PERBEDAAN KETERAMPILAN BERPIKIR KREATIF DITINJAU DARI EMOSI ANAK DALAM BERMAIN KONSTRUKTIF - Taruli Marito Silalahi (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2020)
Abstract Creative thinking skills can be developed early. Emotions play a role in shaping children's creative thinking skills. The purpose of this study is to analyze the differences early childhood creative thinking skills in terms of their emotional state through constructive play activities. This research is quantitative descriptive research. The study population is all children in group B aged 5-6 years totaling 80 childrens. Sampling is Purposive Sampling technique. The study was conducted at the Anak Raja Kindergarten in Medan. Data collection techniques using portfolio and observation techniques. Portfolio data were analyzed descriptively while observation data were analyzed to test hypotheses with Independent T-Test using SPSS 23. The results showed that the average creative thinking skills of children who play constructive with positive emotions were higher with an average value of 15.12 or located in the creative category. While the creative thinking skills of children with negative emotions in constructive play are categorized as less creative, because they obtain an average score of 9.28. Independent T-Test parametric test results are Sig. (2-tailed) 0.00 < from 0.05 so it was decided that Ha which reads